Noninvasive assessment of myocardial fibrosis in patients with obstructive hypertrophic cardiomyopathy. Issue 8 (24th December 2013) - Almaas, Vibeke M; Haugaa, Kristina H; Strøm, Erik H; Scott, Helge; Smith, Hans-Jørgen; Dahl, Christen P; Geiran, Odd R; Endresen, Knut; Aakhus, Svend; Amlie, Jan Peder; Edvardsen, Thor
Abstract : Objective: Late gadolinium enhancement cardiac magnetic resonance (LGE-CMR) imaging is the reference standard for non-invasive assessment of fibrosis. In hypertrophic cardiomyopathy (HCM) patients the histological substrate for LGE is still unknown. The aim of this study was to assess the ability of LGE and strain echocardiography to detect type and extent of myocardial fibrosis in obstructive HCM patients undergoing septal myectomy. Methods: Thirty-two HCM patients (age 60±10) were included in this cross-sectional study and preoperatively examined by speckle-tracking strain echocardiography and LGE-CMR (n=21). Histological fibrosis was classified as interstitial, replacement and total. Results: Histological fibrosis was present in 31 patients. The percentage of total, interstitial and replacement fibrosis was 15(7, 31)%, 11(5, 24)% and 3(1, 6)%, respectively. Reduced longitudinal septal strain correlated with total (r=0.50, p=0.01) and interstitial (r=0.40, p=0.03), but not with replacement fibrosis (r=0.28, p=0.14). Septal LGE was detected in 13/21 (62%), but percentage LGE did not correlate with total fibrosis (r=0.25, p=0.28). Extent of fibrosis did not differ between patients with and without septal LGE (20(9, 58)% versus 14(5, 19)% p=0.41). Patients with ventricular arrhythmias (n=8) had lower septal longitudinal strain and increased extent total and interstitial fibrosis in myectomy specimens, but no differences were demonstrated in LGE. Reduced longitudinal septal strain and increased extent of interstitial fibrosis predicted ventricular arrhythmias independently of age and gender. Conclusions: In myectomised HCM patients, reduced longitudinal septal strain correlated better with interstitial and total fibrosis in myectomy specimens, and was a more powerful tool to predict arrhythmias than LGE.